2020
DOI: 10.1177/1836939120966079
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Aboriginal families’ and children’s developing sense of belonging at KindiLink

Abstract: This paper reports on findings from four case studies, as part of a large-scale study undertaken to evaluate the KindiLink initiative across Western Australia in remote, regional and metropolitan communities. KindiLink is an educator-led playgroup initiative in public school sites in Western Australia targeted at Aboriginal children and their families. KindiLink aims included the cultivation of Aboriginal families’ and children’s developing sense of belonging and engagement at their local primary school. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 19 publications
0
24
0
2
Order By: Relevance
“…A triadic approach, involving children, families and educators, rather than only children and educators, is indicated. The ABCEDARIAN, HIPPY and High Scope initiatives have operated on this basis for a number of years (Fisher et al, 2020), as do more recent approaches in Australia, including Kindilink (Barblett et al, 2020) and Families as First Teachers (Gapany et al, 2021). The triadic potential of school playgroups is worthy of further attention, particularly given that these groups are likely accessible to children and families in communities in which schools are already operating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A triadic approach, involving children, families and educators, rather than only children and educators, is indicated. The ABCEDARIAN, HIPPY and High Scope initiatives have operated on this basis for a number of years (Fisher et al, 2020), as do more recent approaches in Australia, including Kindilink (Barblett et al, 2020) and Families as First Teachers (Gapany et al, 2021). The triadic potential of school playgroups is worthy of further attention, particularly given that these groups are likely accessible to children and families in communities in which schools are already operating.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, school playgroups have been adapted as a model for increasing the participation of Aboriginal and Torres Strait Islander (ATSI) children and families in ECEC. The ‘Kindilink’ (Barblett et al, 2020) and ‘Families as First Teachers’ (Gapany et al, 2021) playgroups have been shown to increase the quality of relationships occurring between ATSI children, families and school communities, especially when Aboriginal Indigenous Education Officers are employed as facilitators.…”
Section: School Playgroupsmentioning
confidence: 99%
“…Eleven studies highlighted that empowering parents with knowledge and skills to support their children's education helped parents engage in their children's learning. Mutual sharing between parents and teachers was a beneficial strategy (Barblett et al, 2020). Teachers shared their expertise on pedagogy (Barblett et al, 2020; Barratt‐Pugh et al, 2021; Leske et al, 2015), parenting, life skills (Benzies et al, 2011; Chodkiewicz et al, 2008; Grace & Trudgett, 2012; Hare, 2011), and leadership skills (Flückiger & Jones, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Mutual sharing between parents and teachers was a beneficial strategy (Barblett et al, 2020). Teachers shared their expertise on pedagogy (Barblett et al, 2020; Barratt‐Pugh et al, 2021; Leske et al, 2015), parenting, life skills (Benzies et al, 2011; Chodkiewicz et al, 2008; Grace & Trudgett, 2012; Hare, 2011), and leadership skills (Flückiger & Jones, 2012). Sharing something by the teachers and making parents feel comfortable practising it was highly effective (Mills, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation